2007
DOI: 10.1063/1.2747594
|View full text |Cite
|
Sign up to set email alerts
|

Improved performance in organic light emitting diodes with a mixed electron donor-acceptor film involved in hole injection

Abstract: Articles you may be interested inElectronic and chemical properties of molybdenum oxide doped hole injection layers in organic light emitting diodes J. Appl. Phys. 105, 033717 (2009); 10.1063/1.3077170Triarylamine siloxane anode functionalization/hole injection layers in high efficiency/high luminance smallmolecule green-and blue-emitting organic light-emitting diodes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…For example, Yuan et al [7] found that the CuPc : C 60 composite could be used to combine with Au, Ag and indium tin oxide (ITO) to form efficient hole injection anode structures for OLEDs. Qin et al applied both the planar and bulk heterojunctions of CuPc and 3, 4, 9, 10 perylenetetracarboxylic dianhydride (PTCDA) to facilitate the hole current generation in OLEDs, and also proposed a mechanism of static-induced and very efficient hole-electron pairs generation between PTCDA and CuPc to explain the experimental phenomena [8,9]. In addition, organic doped p-n heterojunctions have been shown to function as an efficient electron injection layer for flexible inverted OLEDs [10].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Yuan et al [7] found that the CuPc : C 60 composite could be used to combine with Au, Ag and indium tin oxide (ITO) to form efficient hole injection anode structures for OLEDs. Qin et al applied both the planar and bulk heterojunctions of CuPc and 3, 4, 9, 10 perylenetetracarboxylic dianhydride (PTCDA) to facilitate the hole current generation in OLEDs, and also proposed a mechanism of static-induced and very efficient hole-electron pairs generation between PTCDA and CuPc to explain the experimental phenomena [8,9]. In addition, organic doped p-n heterojunctions have been shown to function as an efficient electron injection layer for flexible inverted OLEDs [10].…”
Section: Introductionmentioning
confidence: 99%
“…the tightly bound hole-electron pairs. Although the hole carrier is always the majority as compared to the electron carrier in OLEDs, the increase of hole current is shown to enable the increase of electron current and thereby improve the hole-electron balance [2,3]. Thus, the amplitude of hole current in OLEDs plays a vital role in determining the device performance.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, athough the barrier height of hole injection remains almost the same and unchanged by the intervention of the p-doped layer, holes can easily tunnel into organic layer of an OLED through the very thin depletion zone formed at the interface of p-doped material and anode even at very low driving voltage [4]. In this chapter, we introduce a method of efficient hole current generation at the interface of electron donor and acceptor, in clear contrast to the above-mentioned hole injection technologies, and discuss its potential applications in OLEDs [5][6][7].…”
Section: Hole Injection In Oledsmentioning
confidence: 99%
“…Recently, the planar donor/acceptor interfaces have been successfully used to realize the ambipolar transport in organic field effect transistors [18,19]. The recent work shows that the planar and mixed interfaces of donor and acceptor can generate very efficient hole current in OLEDs [5][6][7]. 1 shows the properties of devices 1, 2, and 4.…”
Section: Hole Generation At the Interfaces Of Electron Donor (Cupc) Amentioning
confidence: 99%
See 1 more Smart Citation